Inflammatory hypoxia induces syndecan-2 expression through IL-1 beta-mediated FOXO3a activation in colonic epithelia - Choi, Sojoong; Chung, Heesung; Hong, Heejeong; Kim, So Yeon; Kim, Seong-Eun; Seoh, Ju-Young; Moon, Chang Mo; Yang, Eun Gyeong; Oh, Eok-Soo (FEDERATION AMER SOC EXP BIOL, 2017)
Chronic inflammation is known to be a key causative factor in tumor progression, but we do not yet fully understand the molecular mechanism through which inflammation leads to cancer. Here, we report that the dextran sulfate sodium (DSS)-induced mouse model of chronic colitis is associated with increases in the serum level of IL-1 beta and the colonic epithelial expression of the cell-surface heparan sulfate proteoglycan, syndecan-2. We further show that IL-1b stimulated the transcription of syndecan-2 via NF-kappa B-dependent FOXO3a activation in CCD841CoN normal colonic epithelial cells and early-stage HT29 colon cancer cells. Inflammatory hypoxia was observed in the colonic epithelia of mice with chronic colitis, suggesting that hypoxic stress is involved in the regulation of syndecan-2 expression. Consistently, experimental inflammatory hypoxia induced hypoxia inducible factor-1 alpha-dependent FOXO3a expression and the p38 MAPK-mediated nuclear localization of FOXO3a. FOXO3a directly mediated syndecan-2 expression in both cell lines and the colonic epithelia of mice with DSS-induced colitis. Moreover, syndecan-2 expression was detected in azoxymethane/ DSS-induced colon tumors. Together, these data demonstrate that inflammatory hypoxia upregulates syndecan-2 via the IL-1 beta-NF-kappa B-FOXO3a pathway. These findings provide new mechanistic insights into inflammatory hypoxia-mediated syndecan-2 expression to connect chronic inflammation and the development of colon cancer.-Choi, S., Chung, H., Hong, H., Kim, S. Y., Kim, S.-E., Seoh, J.-Y., Moon, C. M., Yang, E. G., Oh, E.-S. Inflammatory hypoxia induces syndecan-2 expression through IL-1b-mediated FOXO3a activation in colonic epithelia. FASEB J. 31, 1516-1530 (2017). www.fasebj.org
Keywords: INTESTINAL INFLAMMATION; CYTOKINE REGULATION; COLORECTAL-CANCER; CELL-MIGRATION; COLITIS; PROMOTES; PHOSPHORYLATION; CARCINOGENESIS; PROLIFERATION; STRESS